(Almost) 50 shades of an ethical situation — international physiotherapists' experiences of everyday ethics: a qualitative analysis. (1st February 2023) - Sturm, Andrea; Edwards, Ian; Fryer, Caroline Elizabeth; Roth, Roswith
ABSTRACT: Introduction: Different cultures and societal structures influence the ethical experiences of physiotherapists. Objective: The study aimed to discover and describe contextual shades of ethical situations experienced by physiotherapists in their global practice. Methods: This paper reports the qualitative analysis of responses to an optional open question in an internationally distributed online survey (ESPI study) with 1, 212 participants from 94 countries. All responses were coded to five categories describing the data's relationship to the survey list of ethical situations. Data that described new ethical situations were analyzed thematically. Results: Three hundred and fifty four individual responses to the optional survey question reported 400 ethical issues. Three hundred and seventy-eight of these issues were associated with the original survey questions. Twenty-two responses raised four new themes of ethical issues: lack of regulatory and/or accreditation policy and infrastructure, lack of recognition of the role and position of physiotherapists in healthcare, economic factors driving the conduct of practice, and political threats. Discussion: Local contexts and pressures of workplaces and societies in which physiotherapists practice make it almost impossible for some practitioners to comply with codes of ethics. Physiotherapists need support and preparation to respond to local affordances and the complexity, ambiguity, and sometimes messiness of ethical situations encountered in their practice. Conclusion: The findings highlight the relevance of cross-cultural research in the field of physiotherapy, and the necessity of investigating and bridging the gap between professional ethics theory and practice in diverse settings.